Building a system for independent assessment of educational results of future teachers - E.N. Perevoshchikova; A.V. Stafeeva; S.V. Frolova; T.A. Chepurnova; E.Yu. Elizarova (Theory and Practice of Physical Culture, 2023)
Objective of the study was the theoretical and methodological substantiation of the construction of a system for independent assessment of the educational results of future teachers (hereinafter referred to as SIA). Methods and structure of the study. The theoretical and methodological basis for creating a system for independent assessment of the educational results of future teachers is systemic, activity-based, competence-based, criteria-based and level-based approaches that allow to define, reveal the essence and describe the following key components of such a system: goals, objects of assessment, assessment tools, assessment procedures and levels of achievement. Results and conclusions. On the basis of the selected approaches, the need to consider three types of student activities is substantiated: educational, practice-oriented, professionally-oriented, the results of which allow us to describe their components in the form of measurable actions and assess the degree of achievement of results. Difficulties associated with the assessment of competencies are identified, and the transition to the use of the concept of educational result is justified. The article presents the author’s approach to the description of the concepts: educational result, invariant form of presentation of the evaluation tool and levels of achievement of the educational result.